2008
DOI: 10.1111/j.1083-6101.2008.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Who plays, how much, and why? Debunking the stereotypical gamer profile

Abstract: Online games have exploded in popularity, but for many researchers access to players has been difficult. The study reported here is the first to collect a combination of survey and behavioral data with the cooperation of a major virtual world operator. In the current study, 7,000 players of the massively multiplayer online game (MMO) EverQuest 2 were surveyed about their offline characteristics, their motivations and their physical and mental health. These self-report data were then combined with data on parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
375
7
22

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 539 publications
(425 citation statements)
references
References 38 publications
21
375
7
22
Order By: Relevance
“…Female players constituted one quarter of our sample, which was consistent with past studies of similar games (Williams et al, 2008). The average age was 23.58 (SD = 4.29), and the average years of education was 14.90 (SD = 2.17), suggesting that the majority of the sample were either in college or college-educated young professionals.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Female players constituted one quarter of our sample, which was consistent with past studies of similar games (Williams et al, 2008). The average age was 23.58 (SD = 4.29), and the average years of education was 14.90 (SD = 2.17), suggesting that the majority of the sample were either in college or college-educated young professionals.…”
Section: Resultssupporting
confidence: 85%
“…The players in our sample were skewed toward the young, educated and affluent, which was consistent with gamer profiles in other countries (Williams et al, 2008). Our recruitment strategy, using a virtual weapon in CR3, could in theory have extracted a heterogeneous sample.…”
Section: Limitations and Future Worksupporting
confidence: 69%
See 2 more Smart Citations
“…However, Kuss and Griffiths (2012) summarized the potential motivations for video game players and found that based on previous research, the motivations to play included personal satisfaction, coping strategies, and socialization (Caplan, Williams, & Yee, 2009;Hussain & Griffiths, 2009;Williams, Yee, & Caplan, 2008). It should also be noted that the methodology utilized in previous studies to assess 'motivation' has not been derived from the work of Skinner (1954) or the field of applied behavior analysis.…”
Section: Assessments Of Video Game Addictionmentioning
confidence: 99%